Quality Monitoring of a FIT-Based Colorectal Cancer Screening Program. (1st March 2019) - Toes-Zoutendijk, Esther; Bonfrer, Johannes M G; Ramakers, Christian; Thelen, Marc; Spaander, Manon C W; Dekker, Evelien; van der Meulen, Miriam P; Buskermolen, Maaike; van Vuuren, Anneke J; Kuipers, Ernst J; van Kemenade, Folkert J; van Velthuysen, Marie-Louise F; et al.
Abstract: BACKGROUND: Quality assessment is crucial for consistent program performance of colorectal cancer (CRC) screening programs using fecal immunochemical test for hemoglobin (FIT). However, literature on the consistency of FIT performance in laboratory medicine was lacking. This study examined the consistency of FIT in testing positive or detecting advanced neoplasia (AN) for different specimen collection devices, lot reagents, and laboratories. METHODS: All participants with a FIT sample with a cutoff concentration of 47 μg Hb/g feces in the Dutch CRC screening program in 2014 and 2015 were included in the analyses. Multivariable logistic regression analyses were performed to estimate the odds ratios of collection devices, reagents, and laboratories on testing positive or detecting AN and positive predictive value (PPV). RESULTS: In total, 87519 (6.4%) of the 1371169 participants tested positive. Positivity rates and detection rates of AN differed between collection devices and reagents (all P < 0.01). In contrast, PPVs were not found to vary between collection devices, reagents, or laboratories (all P > 0.05). Positivity rates showed a small difference for laboratories ( P = 0.004) but not for detection rates of AN. Size of the population affected by the deviating positivity rates was small (0.1% of the total tested population). CONCLUSIONS: Variations were observed in positivity and detection rates between collection devices and reagents, but there was no detected variation in PPV. Although the overall population effect of these variations on the screened population is expected to be modest, there is room for improvement.